Ethical moral knowledge in nursing students - Cunha, Madalena (2015)
Abstract: INTRODUCTION: Ethical/moral education is essential to design a scientific course in the health area, as well as for the development of the profession sustained on scientific evidence and best clinical practices. OBJECTIVE: To assess the level of ethical/moral knowledge; to determine if age and gender influence the level of ethical/moral knowledge. METHODS: Descriptive-analytic, cross-sectional study with a non-probabilistic sample of 85 students enrolled in the 1st cycle of the nursing degree. RESULTS: It was found that most students (55.3%) expressed a positive understanding of ethical and moral knowledge. The remaining students manifest a knowledge deficit (44.7%). Male students have a better knowledge (76.9% vs. 51.4%), and women are more highly represented in the group with insufficient knowledge (48.6% vs. 23.1%). Students with more hours of training hold better knowledge of professional duties. CONCLUSIONS: The results suggest that nursing students have ethical/moral knowledge appropriate to the training course attended, demonstrating that the educational intervention promotes ethically driven training for care.